On the Relationship between Trade Openness and Government Size - Mohammad Farhad; Michael Jetter (Center for Economic Studies and ifo Institute (CESifo), 2019)
Does trade openness systematically imply bigger governments, as proposed by Rodrik (1998)? This paper presents a novel and more refined explanation for when and why international trade may enlarge the public sector. We propose that trade openness is associated with bigger governments if (i) the price volatility of a country's export basket is substantial and (ii) the country is democratic. The first condition satisfies the prior that open trade barriers indeed introduce uncertainty and external risk – something that is not necessarily the case for all trade. The second condition ensures that the people's desire for greater economic security can be realized through government spending. Empirical evidence for 143 countries (accounting for approximately 96 percent of world population) from 2000-2016 is consistent with this hypothesis. Exploring areas of public spending, we find intuitive patterns: Consistent with the compensation hypothesis, government spending on economic affairs and housing increases significantly with trade openness, whereas public spending on education, health care, and the military are not immediately concerned. As with our general result, this is only the case in democracies that are subject to high price volatility on the global market.
Keywords: F14; F41; H10; 330; economic globalization; trade openness; government size; export price volatility; democracy